Even Power Weighted Generalized Inverse Weibull Distribution - Rana H. Mutlk, AwatifR.Al-Dubaicy (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this search a new even-power weighted generalized Inverse Weibulldistribution is derived,and some statistical properties of this distribution are discussed, such as [cumulative, probability generating, moment generating, reliability, and Entropy functions] and other properties,scale parameter for this distribution has been estimated by using two methods[Jackknife MaximumLikelihoodestimationand maximum likelihood],thena comparisons has been made between the results we obtained from simulation using MSE criteria to show the best estimator for the scale parameter.